PENGARUH BUDAYA KERJA, LINGKUNGAN KERJA DAN TUNJANGAN KINERJA TERHADAP KINERJA MELALUI KEPUASAN PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN MOJOKERTO - Agung Widyanarko; Sukesi Sukesi (IDEI: Jurnal Ekonomi & Bisnis, 2020)
Employee performance affects how much employees contribute to the organization. Performance affects the results or goals of the organization if performance is poor then organizational goals cannot be achieved. Many things that greatly affect an employee's performance include internal and external factors. The purpose of this study was to analyze the influence of work culture, work environment and performance benefits on job satisfaction and employee performance at the Mojokerto Regency Ministry of Religion Office.This type of research uses quantitative research, which was carried out within the Mojokerto Regency Ministry of Religion Office. Hypothesis testing using t test. The analysis technique used to test and prove hypotheses is structural equation modeling analysis with Smart PLS statistical tools.The results showed that work culture and performance benefits were statistically proven to have an influence on employee satisfaction. While the work environment does not have a significant effect on employee satisfaction at the Mojokerto Regency Ministry of Religion Office. Work culture, work environment and performance benefits are statistically proven to have a significant influence on employee performance. And employee job satisfaction is statistically proven to have a significant effect on employee performance at the Mojokerto Regency Ministry of Religion Office.